Analysis of Influencing Factors Consumers in Decision to Purchase Honda PCX Motorcycle - Muhammad Naufal; Dicky Wisnu Riyanto; R Iqbal Robbie (Universitas Muhammadiyah Malang, 2021)
This research aims to find out the effect of product quality, price, and promotion on honda PCX purchasing decisions on Gresik Motorcycle MPM Dealers/ in this study using the type of descriptive research and population used by Honda PCX motorcycle users whose samples can be conflated using calculations into 96 rounded into 100 samples. Sampling techniques in this study are purposive sampling which has criteria on the respondents of this study and the analytical tools used are intrusion test, normality test, multiple linear regression test and hypothesis test where the results of this study are a cauldron of products, prices, and promotions have a significant and simultaneous positive influence on honda PCX purchase decisions at Gresik Motor MPM Dealers